DEVELOPMENT STRATEGIES OF SMALL MEDIUM MICRO ENTERPRISES (SMEs) LOW-INTEREST LOANS - ., Zakiatuzzahrah (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2016)
ABSTRACT The presence of SMEs not only in order to increase revenue but also to ensure equal distribution of income. This is understandable because the SMEs sector involves a lot of people with a variety of business cases. The government expects an independent and resilient SMEs can flourish and encourage regional and national economy. Support for SMEs must of course be immediately supported by the easiness for SMEs in obtaining venture capital. With the SMEs loans will increase the pace of the economy, which in turn will increase the prosperity and welfare. Keywords : strategy, development, UMKM, bank credit. STRATEGI PENGEMBANGAN USAHA UMKM MELALUI KREDIT BUNGA RENDAH ABSTRAK Kehadiran UKM bukan saja dalam rangka peningkatan pendapatan tapi juga dalam rangka pemerataan pendapatan. Hal ini bisa dimengerti karena sektor UKM melibatkan banyak orang dengan beragam usaha. Pemerintah mengharapkan UMKM yang mandiri, tangguh dapat berkembang, mendorong perekonomian regional serta nasional. Dukungan terhadap UMKM ini tentunya harus segera diwujudkan dengan cara memberi kemudahan-kemudahan bagi UMKM dalam mendapatkan modal usaha. Dengan adanya kredit UKM akan meningkatkan laju perekonomian, sehingga pada akhirnya akan meningkatkan kemakmuran dan kesejahteraan rakyat. Kata kunci : strategi, UMKM, kredit perbankan.